A Minimum Temporal Window for Direction Detection of Frequency-Modulated Sweeps: A Magnetoencephalography Study - Kung, Shu-Jen; Wu, Denise H.; Hsu, Chun-Hsien; Hsieh, I-Hui (Frontiers in Psychology, 2020)
The ability to rapidly encode the direction of frequency contour contained in frequency-modulated (FM) sweeps is essential for speech processing, music appreciation, and conspecific communications. Psychophysical evidence points to a common temporal window threshold for human listeners in processing rapid changes in frequency glides. No neural evidence has been provided for the existence of a cortical temporal window threshold underlying the encoding of rapid transitions in frequency glides. The present magnetoencephalography study used the cortical mismatch negativity activity (MMNm) to investigate the minimum temporal window required for detecting different magnitudes of directional changes in frequency-modulated sweeps. A deviant oddball paradigm was used in which directional upward or downward frequency sweep serves as the standard and the same type of sweep with the opposite direction serves as its deviant. Stimuli consisted of unidirectional linear frequency-sweep complexes that swept across speech-relevant frequency bands in durations of 10, 20, 40, 80, 160, and 320 ms (with corresponding rates of 50, 25, 12.5, 6.2, 3.1, 1.5 oct/s). The data revealed significant magnetic mismatch field responses across all sweep durations, with slower-rate sweeps eliciting larger MMNm responses. A greater temporally-related enhancement in MMNm response was obtained for rising but not falling frequency sweep contours. A hemispheric asymmetry in the MMNm response pattern was observed corresponding to the directionality of frequency sweeps. Contrary to psychophysical findings, we report a temporal window as short as 10 ms sufficient to elicit a robust MMNm response to a directional change in speech-relevant frequency contours. The results suggest that auditory cortex requires extremely brief temporal window to implicitly differentiate a dynamic change in frequency of linguistically-relevant pitch contours. That the brain is extremely sensitive to fine spectral changes contained in speech-relevant glides provides cortical evidence for the ecological importance of FM sweeps in speech processing.